THE INFLUENCE ANALYSIS OF LIQUDITY LEVEL, LEVERAGE AND LEVEL OF CORPORATE ACTIVITY TO ECONOMIC PROFITABILITY OF PT. PT KOBEXINDO TRAKTOR, Tbk, 2016/2017 - Situmorang, Humala (Universitas Kristen Indonesia, 2018)
This study aims to determine the factors causing the reducing in the ability of companies in obtaining profit as measured by economic profitability as a dependent variable. These factors are the level of liquidity, leverage, and level of corporate activity as independent variables. The research method used is descriptive, data collected based on secondary data derived from annual financial statements of 2016 and 2017, and using multiple regression analysis. The results of the analysis concluded that the level of liquidity, leverage and level of company activity partially or simultaneously known through multiple regression analysis has no effect on economic profitability of PT. Kobexindo Traktor, Tbk Keywords: Level of liquidity, leverage, activity level and economic profitability of company